2008
DOI: 10.1007/s11121-007-0079-0
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Risk Assessment to Predict Recurrent Maltreatment: A Classification and Regression Tree Analysis (CART)

Abstract: Research has suggested that recurrent maltreatment may be best predicted by a combination of factors that vary across families. The present study set out to determine whether a pattern-centered analytic approach would better predict families at high risk for recurrence when compared to logistic regression methods. Archival data from substantiated investigations during 2003 were collected from a Connecticut Department of Children and Families county branch. Families (n=244) with a substantiated index case were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
59
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 40 publications
9
59
1
Order By: Relevance
“…In contrast, research on re-entry following reunification has tended to focus more on caregiver mental health, family stressors such as poverty, and case variables such as type of maltreatment (e.g., neglect), substantiation status, and prior Child Protective Services (CPS) involvement (Connell, Bergeron, Katz, Saunders, & Tebes, 2007; Connell et al, 2009; Drake, Jonson-Reid, & Sapokaite, 2006; Hindley, Ramchandani, & Jones, 2006; Sledjeski, Dierker, Brigham, & Breslin, 2008). Adoption research, on the other hand, has found evidence that older child age, behavioral problems, and placement with a nonrelative predict disruption (Coakley & Berrick, 2008; Rushton & Dance, 2006; Smith, Howard, Garnier, & Ryan, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, research on re-entry following reunification has tended to focus more on caregiver mental health, family stressors such as poverty, and case variables such as type of maltreatment (e.g., neglect), substantiation status, and prior Child Protective Services (CPS) involvement (Connell, Bergeron, Katz, Saunders, & Tebes, 2007; Connell et al, 2009; Drake, Jonson-Reid, & Sapokaite, 2006; Hindley, Ramchandani, & Jones, 2006; Sledjeski, Dierker, Brigham, & Breslin, 2008). Adoption research, on the other hand, has found evidence that older child age, behavioral problems, and placement with a nonrelative predict disruption (Coakley & Berrick, 2008; Rushton & Dance, 2006; Smith, Howard, Garnier, & Ryan, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…CART analysis and related approaches have long been used in the areas of medical and marketing decision-making research, and have gained increasing popularity within the human services field, including child welfare and mental health (Alegria et al, 2004; Dean et al, 2009; Frisman, Prendergast, Lin, Rodis, & Greenwell, 2008; Johnson, Brown, & Wells, 2002; Kerby, 2003; Kriston, Berner, Ruf, Mundle, & Härter, 2008; Mann et al, 2008; Montoya, 2008; Müller, Weijers, Böning, & Wiesbeck, 2008; Neuner, Schmid, Wolfersdorf, & Spiessl, 2008; Seroczynski, Cole, & Maxwell, 1997; Sledjeski et al, 2008; Stice, Presnell, & Spangler, 2002; Swan, Jack, Javitz, McAfee, & McClure, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Child welfare caseworkers are asked by the state to provide resources to prevent future episodes of maltreatment and to remedy the “conditions that brought the children and their family to the attention of the agency” (USDHHS, 2015). Child welfare response to maltreatment is guided by administrative data describing the demographics (race, age, marital status); social risk indicators (caregiver mental health, substance use or abuse, family violence); and case characteristics (abuse type, severity, chronicity) closely associated with recidivism (Dakil et al, 2011; Drake & Jonson-Reid, 1999; Horwitz et al, 2011; Jonson-Reid, Emery, Drake, & Stahlschmidt, 2010; Shlonsky, 2007; Sledjeski, Dierker, Brigham, & Breslin, 2008). This aggregate data guides critical safety decisions regarding the need for out-of-home placement of a child or for protective orders against a violent caregiver.…”
mentioning
confidence: 99%
“…As Peddle, Wang, Diaz, and Reid (2002) noted, prevention activities must address risk factors, and there is an increasing recognition that assessment procedures need to be empirically valid (Shlonsky & Wagner, 2005). However, there is currently no standard risk assessment tool to inform caseworkers about case planning (Sledjeski, Dierker, Brigham, & Breslin, 2008).…”
mentioning
confidence: 99%